REVISTING THE RELATIONSHIPS BETWEEN BROADBAND DIFFUSION AND REGIONAL SYSTEM DEVELOPMENT: A PRIMER - Sylvie Occelli; Alessandro Sciullo (European Regional Science Association (ERSA), 2011)
As they create generative conditions for socioeconomic development ICTs and broadband technology, can be understood as an innovation kernel for system evolution. Whereas for a regional system (a local area), technological progress may at certain times be regarded as exogenous, information endowments and expected level of functionalities are not. An innovation kernel, in fact, cannot exist outside the organization of the regional/local system which it belongs to. To grow and deploy its potentials, a fertile environment capable to adapt pro-actively to the changes it produces is needed. In this paper the conceptual underpinnings of an innovation kernel are overviewed and their relationships with those conventionally addressed in regional science studies briefly discussed. Bbuilding upon the IRES research undertaken as a part of the Piedmont ICT Observatory activities, an effort is made to pinpoint the determinants and processes of regional development on which an innovation kernel would encroach. A conceptual framework is outlined which makes it possible to elicit some main relationships between ICTs, broadband and developmental processes in a regional system.
Keywords: 330